2017
DOI: 10.1136/svn-2017-000090
|View full text |Cite
|
Sign up to set email alerts
|

Recanalisation therapy in patients with acute ischaemic stroke caused by large artery occlusion: choice of therapeutic strategy according to underlying aetiological mechanism?

Abstract: Various mechanisms underlie causative large artery occlusion (LAO) in patients with acute ischaemic stroke. Cardioembolic and atherosclerotic occlusions are the two most common types. The pathophysiological changes and responses to mechanical thrombectomy (MT) and antithrombotic treatments including thrombolysis, antiplatelet and anticoagulation therapy may vary among patients with different aetiological mechanisms of occlusion. Atherosclerotic occlusion is inclined to have relatively abundant collaterals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 73 publications
0
14
0
1
Order By: Relevance
“…This study was originally contrived from the necessity to enhance the preprocedural determination of occlusion pathomechanism in endovascular treatment of LVO. Because the optimal endovascular strategy—which includes selection of the most effective endovascular modality and when to switch from one modality to another—depends on the type of occlusion pathomechanism, the earlier determination of occlusion pathomechanism can be crucial in attaining significant recanalization [ 18 , 19 ]. However, unfortunately, there have been only a few practical factors identified that we can rely on to identify occlusion pathomechanism before an endovascular procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This study was originally contrived from the necessity to enhance the preprocedural determination of occlusion pathomechanism in endovascular treatment of LVO. Because the optimal endovascular strategy—which includes selection of the most effective endovascular modality and when to switch from one modality to another—depends on the type of occlusion pathomechanism, the earlier determination of occlusion pathomechanism can be crucial in attaining significant recanalization [ 18 , 19 ]. However, unfortunately, there have been only a few practical factors identified that we can rely on to identify occlusion pathomechanism before an endovascular procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Early reperfusion following ischemia triggers several oxidative, apoptotic, and inflammatory cellular responses leading to reperfusion injury. [9] Oxidative stress is believed to be the major event during this process because reperfusion stimulates an overproduction of a series of reactive oxygen species. [10] The inflammatory response following ischemic brain injury also plays a vital role in the pathogenesis of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recurrent risks in patients with mild stenosis need to be fully appreciated in future studies, so that high-risk patients would not be missed because of artificially graded severity of ICAS by the degree of luminal stenosis [13]. And then, different stroke mechanisms accompany with ICAS, and different aetiological mechanisms has significant clinical implications [15]. Recently study show Interleukin-33 (IL-33) and levels of fibrinogen after anticoagulation were related to ischemic stroke [16,17].…”
Section: Discussionmentioning
confidence: 99%